Multi-omic analysis suggests tumor suppressor genes evolved specific promoter features to optimize cancer resistance. Issue 5 (30th March 2021) - Huang, Dan; Wang, Xiansong; Liu, Yingzhi; Huang, Ziheng; Hu, Xiaoxu; Hu, Wei; Li, Qing; Chan, Hung; Zou, Yidan; Ho, Idy H T; Wang, Yan; Cheng, Alfred S L; et al.
Abstract: Tumor suppressor genes (TSGs) exhibit distinct evolutionary features. We speculated that TSG promoters could have evolved specific features that facilitate their tumor-suppressing functions. We found that the promoter CpG dinucleotide frequencies of TSGs are significantly higher than that of non-cancer genes across vertebrate genomes, and positively correlated with gene expression across tissue types. The promoter CpG dinucleotide frequencies of all genes gradually increase with gene age, for which young TSGs have been subject to a stronger evolutionary pressure. Transcription-related features, namely chromatin accessibility, methylation and ZNF263-, SP1-, E2F4- and SP2-binding elements, are associated with gene expression. Moreover, higher promoter CpG dinucleotide frequencies and chromatin accessibility are positively associated with the ability of TSGs to resist downregulation during tumorigenesis. These results were successfully validated with independent datasets. In conclusion, TSGs evolved specific promoter features that optimized cancer resistance through achieving high expression in normal tissues and resistance to downregulation during tumorigenesis.